Revolutionizing Industries: The Role of Technological Innovations in Modern Business Practices - Nkrumah, Kwame; Agyemang, Akosua (Etunas Sukses Sistem, 2025)
Technological innovation has emerged as a critical driver in transforming modern business practices across the globe. This study investigates the extent to which technological advancements have reshaped industrial operations and business strategies within the Cameroonian context. Using a mixed-methods approach, we collected data from 150 businesses across various sectors, complemented by in-depth interviews with industry leaders and technology stakeholders. The findings reveal a strong correlation between the adoption of emerging technologies—such as artificial intelligence, cloud computing, and automation—and improvements in productivity, operational efficiency, and market competitiveness. However, the study also highlights persistent challenges, including infrastructure deficits, limited digital literacy, and regulatory constraints that hinder full-scale adoption. Our analysis underscores the need for targeted policy reforms, capacity-building initiatives, and strategic investments to foster a more innovation-friendly ecosystem. This research contributes to the growing body of knowledge on digital transformation in emerging economies and offers actionable insights for business leaders, policymakers, and development practitioners aiming to harness technology for sustainable industrial growth.